Project value determinants in organizations - Jolanta Walas-Trębacz; Katarzyna Bartusik (Zeszyty Naukowe Małopolskiej Wyższej Szkoły Ekonomicznej w Tarnowie, 2019)
The article discusses issues related to project value and factors affecting the creation of project value. Based on in-depth literature analysis, approaches to defining project value and project value management are presented. The results of empirical research based on the developed methodology and selected research instruments used in the study of 80 organizations were presented. The analysis of research results leads to the conclusion that the value of the project is influenced by a lot of internal and external determinants. A diagnosis of the level of determinants in the organization allows project managers to correctly and gradually plan the value of the project and to efficiently and effectively implement individual phases of project value management, as well as make decisions regarding raising this value in the future.